2017
DOI: 10.1051/0004-6361/201731334
|View full text |Cite
|
Sign up to set email alerts
|

CO emission tracing a warp or radial flow within ≲100 au in the HD 100546 protoplanetary disk

Abstract: We present spatially resolved Atacama Large Millimeter/submillimeter Array (ALMA) images of 12 CO J = 3 − 2 emission from the protoplanetary disk around the Herbig Ae star, HD 100546. We expand upon earlier analyses of this data and model the spatiallyresolved kinematic structure of the CO emission. Assuming a velocity profile which prescribes a flat or flared emitting surface in Keplerian rotation, we uncover significant residuals with a peak of ≈ 7δv, where δv = 0.21 km s −1 is the width of a single spectral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 68 publications
5
50
0
Order By: Relevance
“…These values are consistent with most reported position angles from previous sub-mm observations of the disc with ALMA; Walsh et al (2014) Panić et al (2014) observed the disc with the MID-infrared Interferometric instrument (MIDI) on the VLT and find a position angle of 145±5 • , their inclination is considerably higher however because their observations probe the inner wall of the disc at 11 au. There is growing evidence for a warp in the disc (Quillen 2006;Panić et al 2010;Walsh et al 2017) which would cause inclination to deviate radially.…”
Section: Coordinates Of Bestmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are consistent with most reported position angles from previous sub-mm observations of the disc with ALMA; Walsh et al (2014) Panić et al (2014) observed the disc with the MID-infrared Interferometric instrument (MIDI) on the VLT and find a position angle of 145±5 • , their inclination is considerably higher however because their observations probe the inner wall of the disc at 11 au. There is growing evidence for a warp in the disc (Quillen 2006;Panić et al 2010;Walsh et al 2017) which would cause inclination to deviate radially.…”
Section: Coordinates Of Bestmentioning
confidence: 99%
“…For example there has been recent evidence of warps from ALMA observations, e.g. this disc (Walsh et al 2017) and T Tauri star AA Tau (Loomis et al 2017). A warp of the inner disc can lead not only to shadowing of the outer disc but potentially even a break of the disc into two distinct planes.…”
Section: Comparison To Previous Asymmetries In Hd 100456mentioning
confidence: 99%
“…The inner disc casts unique shadows on the outer disc, constraining the relative inclination between the two (Min et al 2017). Relative inclinations have been measured from 30 • for DoAR 44 (Casassus et al 2018) to 45 • for AA Tau (Loomis et al 2017), 70 • for HD 142527 (Marino et al 2015), 72 • for HD 100453 Benisty et al (2017) and up to 80 • for HD 100546 (Walsh et al 2017). Numerical simulations suggested that such an arrangement may be generated through gravitational interaction with an inclined binary.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow lane shadows have been observed in scattered light observations of a number of protoplanetary discs (Marino et al 2015;Walsh et al 2017;Benisty et al 2018;van der Plas et al 2019). These indicate a large (∼ 70 − 90 • relative misalignment between the inner and outer disc (Marino et al 2015;Walsh et al 2017;Pinilla et al 2018).…”
Section: Introductionmentioning
confidence: 94%